A comparative study of the Malaysian Garden Concept (MGC) criteria application on the public parks - Zakaria, Ahmad Zamil; Dali, Melasutra Md; Hussein, Hazreena (Science and Engineering Research Support Society, 2020)
Today there are public parks that are named with the Malaysian Garden. Researchers need to determine whether the design of the public parks is following the MGC guidelines provided by the National Landscape Department. Public parks that use the name of the Malaysian Garden / "Taman Malaysia" will be an example of MGC gardens. The main objective of this study is to find out the level of use of MGC criteria in public parks that have used the Malaysian Garden as its name. In this paper, researchers have used qualitative methods, namely, observation and interview experts. The results of the study found that the application of MGC criteria is placed in the weak category. However, three main factors are the cause of non-compliance with the MGC criteria. Furthermore, this study has explained to us the criteria that underlie the design of the MGC. © 2020 SERSC.